High-hardness electrophoresis confining liquid for aluminum alloy micro-arc oxidation film and preparation method and electrophoresis construction method of high-hardness electrophoresis confining liquid

By using high-hardness electrophoretic sealing liquid and electrophoretic construction method on the aluminum alloy microarc oxide film layer, a hard wear-resistant particle group mixed with organic and inorganic is formed, which solves the problem of degradation of hardness and wear resistance of the aluminum alloy microarc oxide film layer, and achieves a significant improvement in hardness, wear resistance and corrosion resistance.

CN119776947AInactive Publication Date: 2025-04-08BADA NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411762747.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The loose porous structure of the micro-arc oxide film layer of aluminum alloy leads to a decrease in its wear resistance and hardness. The existing sealing process improves corrosion resistance while also affects hardness and wear resistance.

Method used

A high-hardness electrophoretic sealing liquid of aluminum alloy microarc oxide film layer is adopted, and its components include Al(NO3)3, ZrOSO4, TiOSO4, calcium lignin sulfonate, H3PO4 and Na2SiO3. It is sealed and cured under alternating current by electrophoretic construction to form a hard wear-resistant particle group mixed with organic and inorganic.

Benefits of technology

It significantly improves the hardness and wear resistance of the microarc oxide layer, while enhancing corrosion resistance, and is environmentally friendly, low-cost and easy to construct.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of aluminum alloy surface treatment, and discloses high-hardness electrophoresis confining liquid for an aluminum alloy micro-arc oxidation film and a preparation method and an electrophoresis construction method of the high-hardness electrophoresis confining liquid. The confining liquid is prepared from the following components: Al (NO3) 3, ZrOSO4, TiOSO4, calcium lignosulphonate, H3PO4 and Na2SiO3; the confining liquid is an inorganic / organic mixed electrophoresis confining liquid, and has the characteristics of environment friendliness, low cost, easiness in construction and capability of remarkably improving the hardness, corrosion resistance and wear resistance of a micro-arc oxidation layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of aluminum alloy surface treatment, and relates to a high-hardness electrophoresis sealing liquid for an aluminum alloy micro-arc oxidation film layer, a preparation method thereof, and an electrophoresis construction method. Background Art

[0002] The micro-arc oxidation film of aluminum alloy can give the aluminum alloy a high hardness, wear resistance and corrosion resistance, so that the aluminum alloy can be more widely used in ships, submersibles, beach sliding equipment and other places. However, the micro-arc oxidation layer is often composed of three layers from the outside to the inside: a loose layer, a dense layer, and an interface layer. The outermost porous and loose loose layer is easy to cause comprehensive corrosion and damage to the overall micro-arc oxidation ceramic layer on the surface after absorbing corrosive substances. In addition, due to its natural loose porous structure, the wear resistance and hardness of the surface layer are reduced. In order to solve this problem, people have developed a variety of sealing processes, including high-temperature boiling, inorganic salt hydrolysis, electrophoresis, sol-gel film filling, chemical nickel plating and other methods; although the above-mentioned treatment methods can improve the corrosion resistance of the aluminum alloy micro-arc oxidation layer, they will also affect the hardness and wear resistance of the aluminum alloy micro-arc oxidation film during the treatment. Summary of the invention

[0003] The present invention overcomes the shortcomings of the prior art and proposes a high-hardness electrophoretic sealing liquid for aluminum alloy micro-arc oxidation film layer, a preparation method thereof, and an electrophoretic construction method; the present invention is achieved through the following technical solutions: A high-hardness electrophoresis sealing liquid for aluminum alloy micro-arc oxidation film, wherein the following components are dissolved in each liter of pure water: Al(NO3)3 5-7g / L ZrOSO4 3-5g / L TiOSO4 3-5g / L Calcium lignin sulfonate 1-2g / L H3PO4 10-15ml / L Na2SiO3 5-8g / L The pH of the electrophoresis blocking solution is 5-6.

[0004] Preferably, Na2SiO3 is water glass with a mass percentage of 35-45%.

[0005] A method for preparing a high-hardness electrophoretic sealing liquid for an aluminum alloy micro-arc oxidation film comprises the following steps: S1. Take 500 ml of pure water, add 10-15 ml of H3PO4, 5-7 g of Al(NO3)3, 3-5 g of ZrOSO4, 3-5 g of TiOSO4, and 1-2 g of calcium lignin sulfonate into the pure water in sequence under stirring, dissolve one raw material and then add the next raw material, stir for 1-2 minutes after all the raw materials are dissolved, and prepare liquid A; S2, dissolving 5-8 g of 35-45% water glass in 100 ml of pure water to obtain liquid B; S3. Add liquid B to liquid A while stirring, add purified water to 1L, and adjust the pH to 5-6 while stirring; S4. After standing for 24 to 26 hours, filter and obtain the clear solution, which is the electrophoresis blocking solution.

[0006] Preferably, the stirring speed in step S3 is 200-300 r / min.

[0007] Preferably, 1N NaOH solution is used to adjust the pH.

[0008] An electrophoretic construction method of a high-hardness electrophoretic sealing liquid for an aluminum alloy micro-arc oxidation film layer comprises the following steps: S1. Use variable frequency AC power supply, hang a group of workpieces at the two poles of the power supply, use constant voltage control, the highest voltage is 11-15V, the frequency is 50-300Hz, and electrophoresis is carried out at room temperature for 10-15min; S2, rinsing the workpiece, and then baking and curing; after curing and drying, cooling to room temperature with the furnace.

[0009] Preferably, after step S2 is completed, a cloth wheel or a hemp wheel is used to polish the surface of the workpiece, and paraffin or paraffin-doped Cr2O3 powder is used for polishing during the polishing process.

[0010] Preferably, the rinsing in step S2 is performed twice with overflow circulating tap water, followed by drying at room temperature for 40-60 minutes and then using high-pressure air to blow away the accumulated water and liquid on the edges, corners, holes and surfaces.

[0011] Preferably, the baking and curing is performed using a step-wise heating curve: Raise the temperature from room temperature to 50°C and keep at 50°C for 15 minutes; Raise the temperature from 50°C to 80°C and keep at 80°C for 20 minutes; Raise the temperature from 80°C to 120°C and keep at 120°C for 20 minutes; Raise the temperature from 120°C to 150°C and keep at 150°C for 20 minutes.

[0012] The beneficial effects of the present invention compared with the prior art are as follows: The high-hardness electrophoretic sealing liquid for aluminum alloy micro-arc oxidation film layer described in the present invention is an inorganic / organic mixed electrophoretic sealing liquid, which is environmentally friendly, low-cost, easy to construct, and can significantly improve the hardness, corrosion resistance and wear resistance of the micro-arc oxidation layer.

[0013] The components of the aluminum alloy micro-arc oxidation film high hardness electrophoretic sealing liquid described in the present invention have a synergistic effect: ①Al(NO3)3: ionizes in an acidic atmosphere to produce Al 3+ First, the ion effect reduces the corrosion and dissolution of the aluminum alloy micro-arc oxide layer by the entire closed liquid. Secondly, when the alternating current is in the negative half cycle, the pH value around the electrode rises. When in an alkaline environment, it reacts with OH - Ion reaction forms Al(NO3)3 gel, and the third one reacts with PO4 3+ The ions combine to form AlPO4 inorganic adhesive substance.

[0014] ②ZrOSO4: ionizes into ZrO in aqueous solution 2+ Cations, on the one hand, can react with water molecules to form substances with condensation network structures; on the other hand, when the alternating current is in the negative half cycle, they are pulled into the micropores of the micro-arc oxidation loose film layer to fill the pores and enhance the hardness and wear resistance.

[0015] ③TiOSO4: Same as ZrOSO4 ④Na2SiO3: forms H2SiO3 with adhesive effect in acidic water solution ⑤H3PO4: On the one hand, it makes the sol sealing liquid system in an acidic state, and on the other hand, it reacts with Al 3+ Forming AlPO4 inorganic adhesive material; ⑥ Calcium lignin sulfonate: ionized to Ca in aqueous solution 2+ and lignin sulfonate anion, Ca 2+ With PO4 3+ and H2O to form Ca(H2PO4)2. In the negative half cycle of AC, Ca 2+ Enter the micropores to form Ca(OH)2·CaSO4 colloidal substances, while the lignin sulfonate anion is an excellent chelating agent that can chelate Ca 2+ 、Ti 4+ 、Zr 4+ 、Al 3+ Plasma enables it to carry out chemical and electrochemical reactions in an orderly manner. On the other hand, excellent anionic surfactants can fully disperse the surrounding colloid particles formed by the reaction. Thirdly, using a water reducer in the curing process after the sealing is completed can greatly improve the density and hardness of the sealing material. Fourthly, the condensation of lignin sulfonate into macromolecules can further enhance the sealing effect. DETAILED DESCRIPTION

[0016] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The technical solutions of the present invention are described in detail below in conjunction with the embodiments, but the scope of protection is not limited thereto.

[0017] Example 1 This embodiment provides a high-hardness electrophoresis sealing liquid for aluminum alloy micro-arc oxidation film, wherein the following components are dissolved in each liter of pure water: Al(NO3)3 5g / L ZrOSO4 5g / L TiOSO4 3g / L Calcium lignin sulfonate 2g / L H3PO4 10ml / L Na2SiO3 8g / L The pH of the electrophoresis blocking solution is 5.

[0018] Among them, Na2SiO3 is water glass with a mass percentage of 35%.

[0019] Example 2 This embodiment provides a high-hardness electrophoresis sealing liquid for aluminum alloy micro-arc oxidation film, wherein the following components are dissolved in each liter of pure water: Al(NO3)3 7g / L ZrOSO4 3g / L TiOSO4 5g / L Calcium lignin sulfonate 1g / L H3PO4 15ml / L Na2SiO3 5g / L The pH of the electrophoresis blocking solution is 6.

[0020] Among them, Na2SiO3 is water glass with a mass percentage of 45%.

[0021] Example 3 This embodiment provides a high-hardness electrophoresis sealing liquid for aluminum alloy micro-arc oxidation film, wherein the following components are dissolved in each liter of pure water: Al(NO3)3 6g / L ZrOSO4 4g / L TiOSO4 4g / L Calcium lignin sulfonate 1g / L H3PO4 12ml / L Na2SiO3 6g / L The pH of the electrophoresis blocking solution is 5.5.

[0022] Among them, Na2SiO3 is water glass with a mass percentage of 40%.

[0023] Example 4 This embodiment provides a method for preparing a high-hardness electrophoretic sealing liquid for an aluminum alloy micro-arc oxidation film. The following components are dissolved in each liter of pure water: (using the component formula of Embodiment 3) S1. Take 500 ml of pure water, add 12 ml of H3PO4, 6 g of Al(NO3)3, 4 g of ZrOSO4, 4 g of TiOSO4, and 1 g of calcium lignin sulfonate into the pure water in sequence under stirring, add the next raw material after one raw material is dissolved, and stir for 1 min after all the raw materials are dissolved to prepare liquid A; S2, dissolving 6 g of 40% water glass by mass in 100 ml of pure water to obtain liquid B; S3. Add liquid B into liquid A while stirring at a speed of 200 r / min, add pure water to 1 L, and adjust the pH to 5.5 with 1N NaOH solution while stirring; S4. After standing for 24 hours, filter to obtain the clarified liquid. The translucent reddish brown liquid is the electrophoresis blocking solution.

[0024] Example 5 This embodiment provides a method for preparing a high-hardness electrophoretic sealing liquid for an aluminum alloy micro-arc oxidation film, wherein the following components are dissolved in each liter of pure water: S1. Take 500 ml of pure water, add 15 ml of H3PO4, 6 g of Al(NO3)3, 4 g of ZrOSO4, 4 g of TiOSO4, and 1 g of calcium lignin sulfonate into the pure water in sequence under stirring, add the next raw material after one raw material is dissolved, and stir for 2 minutes after all the raw materials are dissolved to prepare liquid A; S2, dissolving 6 g of 40% water glass by mass in 100 ml of pure water to obtain liquid B; S3. Add liquid B into liquid A while stirring at a speed of 300 r / min, add pure water to 1 L, and adjust the pH to 6 with 1N NaOH solution while stirring; S4. After standing for 24 hours, filter to obtain the clarified liquid. The translucent reddish brown liquid is the electrophoresis blocking solution.

[0025] Example 6 An electrophoretic construction method of a high-hardness electrophoretic sealing liquid for an aluminum alloy micro-arc oxidation film layer, wherein the specific process flow is: a. aluminum alloy workpiece → b. surface cleaning → c. micro-arc oxidation → d. water washing → e. high-pressure air drying → f. electrophoretic sealing → g. curing → h. mechanical polishing → j. inspection; Steps ad are the same as the conventional aluminum alloy micro-arc oxidation process; Step e is high-pressure air drying: Use 0.3-0.5MPa dry and clean high-pressure air to dry all surfaces, corners, and holes of the micro-arc oxidation workpiece so that there is no water accumulation in these positions.

[0026] Step f: Electrophoresis sealing: A variable frequency AC power supply is used, and a group of workpieces can be hung at both poles of the power supply. The area difference of the workpieces at the two poles is less than 15%. Constant voltage control is used, and the maximum voltage is controlled between 11-15V, the frequency is 200Hz, and the treatment is carried out at room temperature for 15 minutes. After the sealing construction is completed, rinse with overflow circulating tap water twice to clean the electrophoresis liquid deposition that is not attached to the surface. After drying at room temperature for 40-60 minutes, use high-pressure air to blow away the accumulated water and liquid on the edges, corners, holes, and surfaces, and start baking and curing. (The sealing liquid used for electrophoresis sealing is prepared in Example 4) Step g: The baking curing adopts a step-type heating curve: Raise the temperature from room temperature to 50°C and keep at 50°C for 15 minutes; Raise the temperature from 50°C to 80°C and keep at 80°C for 20 minutes; Raise the temperature from 80°C to 120°C and keep at 120°C for 20 minutes; Raise the temperature from 120°C to 150°C and keep at 150°C for 20 minutes.

[0027] After the curing and drying is completed, the furnace is cooled to room temperature.

[0028] h Step - Mechanical Polishing The workpiece surface is polished with a cloth wheel or a hemp wheel, and paraffin or paraffin doped with Cr2O3 powder can be used for polishing during the polishing process.

[0029] The working principle and process of the sealing liquid under the action of alternating current are as follows: ①Ion state when no power is applied: Al(NO3)3 →Al 3+ +3NO3 - ZrOSO4→ZrO 2+ +SO4 2- TiOSO4→TiO 2+ +SO4 2- Na2SiO3+2H + →2Na + + H2SiO3 Na2SiO3→2Na + +SiO3 2- H3PO4 →3H + +PO4 3- Calcium lignin sulfonate (M-Ca) → M n- +mCa 2+ M n- +Al 3+ +ZrO 2+ +TiO 2+ ⇌ M x Al 3+ y (ZrO 2+ ) z (TiO 2+ ) k H2O ⇌ H + +OH - ② When the workpiece is in the positive half cycle of AC: In the first stage: 4OH--e→2H2O+O2↑ (anode oxygen evolution [OH - ] Reduce pH decrease) 2H + +SO4 2- →H2SO4 2H + +SiO3 2- →H2SiO3 Ca 2+ +SO4 2- +PO4 3- →CaSO4+Ca3(PO4)2 Al 3+ +PO4 3- →AlPO4 Oxygen evolution at the positive electrode, [OH - ]Reduced [H + ] increases relatively, and the negative ions move toward the positive electrode and are finally pulled into the micropores of the micro-arc oxidation film to react and form insoluble Ca3(PO4)2 and colloidal H2SiO3, CaSO4, AlPO4 and other substances as well as lignin sulfonate calcium (abbreviated as: wood calcium) (M-Ca) polymers [M] x .

[0030] ③When the workpiece is in the negative half cycle of AC: 2H + +2e→H2↑ Al 3+ +3OH - →Al(OH)3 Ca2+ +2OH - →Ca(OH)2 ZrO 2+ +OH - →Zr(OH)4 TiO 2+ +OH - →Ti(OH)4 Oxygen evolution at the negative electrode, [H + ] decreased, [OH - ] increases relatively, forming Ca(OH)2 slightly soluble substances and Al(OH)3, Zr(OH)4, and Ti(OH)4 with adsorptive precipitates.

[0031] ④ When the workpiece is in the second stage of the positive half cycle of AC power: Al+O2→Al2O3+Q (i.e. heat) (anodic oxidation) Al(OH)3≜Al2O3·n'H2O Zr(OH)4≜ZrO2·m'H2O Ti(OH)4≜TiO2·x'H2O H2SiO3≜SiO2+H2O Finally, CaSO4, AlPO4, H2SiO3 are used as binders, Al2O3, ZrO2, TiO2, SiO2, Ca3(PO4)2 are used as filler particles, and lignin polymer [M] is used as a binder. x The organic and inorganic mixed hardness and wear-resistant particles are mixed in the glue to fill and seal the pores in the loose layer of the micro-arc oxidation layer.

[0032] Comparative Example 1 An electrophoretic construction method of a high-hardness electrophoretic sealing liquid for an aluminum alloy micro-arc oxidation film layer, wherein the specific process flow is the same as that of Example 6, except that the electrophoretic sealing liquid is different. The electrophoretic sealing liquid used in Comparative Example 1 is the existing conventional Ni(Ac)2 hydrolyzed salt.

[0033] Performance test: The surface properties of the workpieces constructed in Example 6 were compared with those of the workpieces constructed in Comparative Example 1. The results are shown in the following table: The above content is a further detailed description of the present invention in combination with a specific preferred embodiment. It cannot be determined that the specific embodiments of the present invention are limited to this. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the present invention, which should be regarded as belonging to the present invention and the scope of patent protection determined by the submitted claims.

Claims

1. A high-hardness electrophoretic sealing liquid for aluminum alloy micro-arc oxidation film, characterized in that: The following components are dissolved in each liter of pure water: Al(NO3)3 5-7g / L ZrOSO4 3-5g / L TiOSO4 3-5g / L Calcium lignin sulfonate 1-2g / L H3PO4 10-15ml / L Na2SiO3 5-8g / L The pH of the electrophoresis blocking solution is 5-6.

2. The high-hardness electrophoretic sealing liquid for aluminum alloy micro-arc oxidation film according to claim 1, characterized in that: Na2SiO3 is water glass with a mass percentage of 35-45%.

3. The method for preparing a high-hardness electrophoretic sealing liquid for an aluminum alloy micro-arc oxidation film as claimed in claim 2, characterized in that: The following steps are involved: S1. Take 500 ml of pure water, add 10-15 ml of H3PO4, 5-7 g of Al(NO3)3, 3-5 g of ZrOSO4, 3-5 g of TiOSO4, and 1-2 g of calcium lignin sulfonate into the pure water in sequence under stirring, dissolve one raw material and then add the next raw material, stir for 1-2 minutes after all the raw materials are dissolved, and prepare liquid A; S2, dissolving 5-8 g of 35-45% water glass in 100 ml of pure water to obtain liquid B; S3. Add liquid B to liquid A while stirring, add purified water to 1L, and adjust the pH to 5-6 while stirring; S4. After standing for 24 to 26 hours, filter and obtain the clear solution, which is the electrophoresis blocking solution.

4. The method for preparing a high-hardness electrophoretic sealing liquid for aluminum alloy micro-arc oxidation film according to claim 3, characterized in that: The stirring speed in step S3 is 200-300 r / min.

5. The method for preparing a high-hardness electrophoretic sealing liquid for aluminum alloy micro-arc oxidation film according to claim 3, characterized in that: 1N NaOH solution was used to adjust the pH.

6. The electrophoresis construction method of the aluminum alloy micro-arc oxidation film layer high hardness electrophoresis sealing liquid as claimed in claim 2, characterized in that: The following steps are involved: S1. Use variable frequency AC power supply, hang a group of workpieces at the two poles of the power supply, use constant voltage control, the highest voltage is 11-15V, the frequency is 50-300Hz, and electrophoresis is carried out at room temperature for 10-15min; S2, rinsing the workpiece, and then baking and curing; after curing and drying, cooling to room temperature with the furnace.

7. The electrophoresis construction method of the aluminum alloy micro-arc oxidation film layer high hardness electrophoresis sealing liquid according to claim 6, characterized in that: After step S2 is completed, a cloth wheel or a hemp wheel is used to polish the surface of the workpiece, and paraffin or paraffin doped Cr2O3 powder is used for polishing during the polishing process.

8. The electrophoresis construction method of the aluminum alloy micro-arc oxidation film layer high hardness electrophoresis sealing liquid according to claim 6, characterized in that: The rinsing in step S2 is performed twice with overflow circulating tap water, followed by drying at room temperature for 40-60 minutes and then using high-pressure air to blow away the accumulated water and liquid on the edges, corners, holes and surfaces.

9. The electrophoresis construction method of the aluminum alloy micro-arc oxidation film layer high hardness electrophoresis sealing liquid according to claim 6, characterized in that: The baking and curing is carried out using a step-by-step heating curve: Raise the temperature from room temperature to 50°C and keep at 50°C for 15 minutes; Raise the temperature from 50°C to 80°C and keep at 80°C for 20 minutes; Raise the temperature from 80°C to 120°C and keep at 120°C for 20 minutes; Raise the temperature from 120°C to 150°C and keep at 150°C for 20 minutes.

Citation Information

Patent Citations

  • Hole sealing treatment method for aluminum alloy micro-arc oxidation ceramic film

    CN112647105A

  • Aluminum alloy micro-arc oxidation film hole sealing treatment method

    CN116791170A